Observation of cosmic ray hadrons at the top of the Sierra Negra volcano in Mexico with the SciCRT prototype. Issue 10 (15th November 2016) - Ortiz, E.; Valdés-Galicia, J.F.; Matsubara, Y.; Nagai, Y.; Hurtado, A.; Musalem, O.; García, R.; Anzorena, M.A.; González, L.X.; Itow, Y.; Sako, T.; Lopez, D.; et al.
Abstract: In this work we report the flux of protons and neutral emission measured at the top of the Sierra Negra volcano at 4600 m.a.s.l. (575 g/cm 2 ), in Eastern Mexico. As an example of the capability of the mini-SciCR as a cosmic ray detector we present the Forbush decrease recorded on March 7, 2012. These data were obtained with a cosmic ray detector prototype called mini-SciCR that was operating from October 2010 to July 2012. Our main aims were to measure the hadronic component flux of the secondary cosmic ray and to show the appropriate performance of all system of the detector. To separate the signals of protons from other charged particles we obtained the energy deposition pattern when they cross the detector using a Monte Carlo simulation, and to separate the signals of neutral emission we used an anticoincidence system between the edge bars and the internal bars of the detector. The mini-SciCR is a prototype of a new cosmic ray detector called SciBar Cosmic Ray Telescope (SciCRT) installed in the same place, which is in the process of calibration. The SciCRT will work mainly as a Solar Neutron and Muon Telescope, it is designed to achieve: (1) larger effective area than the current Solar Neutron Telescope, (2) higher energy resolution to determine the energy spectrum of solar neutrons, (3) lower energy threshold, and (4) higher particle identification ability.